Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata) - Grischenko, Andrei V.; Gordon, Dennis P.; Taylor, Paul D.; Kuklinski, Piotr; Denisenko, Nina V.; Spencer-Jones, Mary E.; Ostrovsky, Andrew N. (Zootaxa, 2022)
Twenty-four Recent species of the boreal-Arctic and Pacific cheilostome bryozoan genus Rhamphostomella are described. The species R. tatarica and R. pacifica are transferred to Rhamphostomella from Posterula and Porella, respectively. Eight species are new: R. aleutica n. sp., R. aspera n. sp., R. commandorica n. sp., R. echinata n. sp., R. microavicularia n. sp., R. morozovi n. sp., R. multirostrata n. sp. and R. obliqua n. sp. Neotypes are selected for six species, and lectotypes for eight species. Mixtoscutella n. gen. is established for several Rhamphostomella-like species, including M. androsovae [formerly Smittina androsovae Gontar], M. cancellata [formerly Escharella porifera forma cancellata Smitt], M. harmsworthi [formerly Schizoporella harmsworthi Waters], M. ovata [formerly Cellepora ovata (Smitt)], and M. ussowi [formerly Schizoporella ussowi (Kluge)]. In addition to taxonomic revision, the morphology (frontal shields, ovicells and multiporous septula), ecology and zoogeography of these cheilostomes are discussed, and identification keys are presented. Most species of Rhamphostomella have broad bathymetric distributions. Some have long protuberances on their basal walls that allow them to grow elevated above allelopathically active substrates such as sponges. The diversity of Rhamphostomella peaks in the northwestern Pacific.